Hubungan Konsumsi Junk Food dengan Menarche Dini pada Remaja Putri di Sekolah Dasar: The Relationship between Junk Food Consumption and Early Menarche in Teenage Girls in Elemementary Schools - Sabrina, Giska; utami, lucia (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
The age of early menarche continues to increase in various places anywhere in Indonesia, especially in big cities, which can be caused by an increase in the frequency of junk food consumption.  Consumption of junk food is favored by people of all ages, including children and adolescents.  Nutritional intake by consuming junk food with too much frequency can be the cause of early menarche.  In addition, junk food can increase obesity and cardiovascular disease, it can also increase the risk of breast cancer and endometrial cancer.          The research was conducted at SDN Kampung Melayu 01, East Jakarta by involving students in grades 4-6 at SDN Kampung Melayu 01, East Jakarta.  The research method used a correlative descriptive quantitative design with a cross-sectional approach.  The sample in this study involved 108 female students with total sampling technique.  The instruments used were menarche status questionnaire and Food Frequency Questionnaire (FFQ).           The results of the Kendal's Tau C correlation test obtained a p-value of 0.243 (> 0.05) which shows there is no significant relationship between junk food consumption and early menarche in teenage girls at SDN Kampung Melayu 01, East Jakarta.            Suggestions for teenage girls to maintain a balanced diet and reduce the consumption of junk food which has an impact on early menarche and health by maintaining a nutritious diet.  Educational institutions can use existing media in schools to convey information on the impact of consuming junk food.